Synthesis and characterization of new benzotriazole derivatives - Radhy, Ahmed W.; Zimam, Ezzat H. (Al-Qadisiyah Journal of Pure Science, 2017)
This research involves synthesis of some derivatives of benzotriazole and new heterocyclic derivatives such as (pyrazoline, pyrimidine, benzopyran) which have chemical and biological importance. The first step, include the synthesis of 1-N-Acetyl-benzotriazole from reaction benzotriazole with acetic anhydride in presence of some drops of sulfuric acid. The second step, include synthesis the a series of Î±,Î²-unsaturated carbonyl compounds (chalcones) ,by consdensation of 1-N-Acetyl-benzotriazole ,with different aromatic aldehydes[ 4-(dimethylamino)benzaldehyde,4-hydroxybenzaldehyde,4-nitrobenzaldehyde,4-clorobenzal dehyde ] to give new chalcone (A ,B ,C ,D) respectively. A. 1-N (3-(4-(dimethylamino phenyl)propenone) Benzotriazole. B. 1-N (3-(4-hydroxyphenyl) propenone) Benzotriazole. C. 1-N (3-(4-nitrophenyl) propenone) Benzotriazole. D. 1-N (3-(4-chlorophenyl) propenone) Benzotriazole. The three step, include the synthesis the A series of different heterocyclic. These compounds (chalcones) were used as precursors in preparation of a number of cyclic organic compounds through their reaction with : 1- hydrazine, Phenyl hydrazine in methanoic acid to form another series of pyrazoline compounds (A1,B1,C1,D1, A2,B2,C2,D2) . 2- thiocemecarbezid to form pyrazoline derivatives compounds (A3,B3,C3,D3). 3- uear,thiouear and guaniden to from pyrimidine derivatives compounds (A4,A5,A6,B4,B5,B6,C4,C5,C6,D4,D5,D6). 4- Resorcinol in Hydrochloric acid to form benzopyran derivatives compounds (A7,B7,C7,D7) .